2022
DOI: 10.1038/s41537-022-00293-1
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo 7-Tesla MRI Investigation of Brain Iron and Its Metabolic Correlates in Chronic Schizophrenia

Abstract: Brain iron is central to dopaminergic neurotransmission, a key component in schizophrenia pathology. Iron can also generate oxidative stress, which is one proposed mechanism for gray matter volume reduction in schizophrenia. The role of brain iron in schizophrenia and its potential link to oxidative stress has not been previously examined. In this study, we used 7-Tesla MRI quantitative susceptibility mapping (QSM), magnetic resonance spectroscopy (MRS), and structural T1 imaging in 12 individuals with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 74 publications
(72 reference statements)
0
20
1
Order By: Relevance
“…Earlier studies on MDD using QSM reported high magnetic susceptibility in the putamen, hippocampus, and thalamus, which is not in agreement with the current results [22]. Further, prior research reported a decrease in magnetic susceptibility in the globus pallidus, left putamen, and left thalamus of rst-episode schizophrenia patients [24] and observed high magnetic susceptibility bilaterally in the putamen of chronic schizophrenia patients [25]. These discrepancies were probably caused by differences in QSM analysis methods used by earlier studies.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Earlier studies on MDD using QSM reported high magnetic susceptibility in the putamen, hippocampus, and thalamus, which is not in agreement with the current results [22]. Further, prior research reported a decrease in magnetic susceptibility in the globus pallidus, left putamen, and left thalamus of rst-episode schizophrenia patients [24] and observed high magnetic susceptibility bilaterally in the putamen of chronic schizophrenia patients [25]. These discrepancies were probably caused by differences in QSM analysis methods used by earlier studies.…”
Section: Discussioncontrasting
confidence: 98%
“…In addition, only a few studies on psychiatric disorders examine the relationship between structural subcortical volume changes and magnetic susceptibility; however, research indicates a negative correlation between volume and magnetic susceptibility in the hippocampus in schizophrenia patients [25]. In neurological studies using amyloid-beta (Aβ) PET, subcortical Aβ is associated with changes in the surface morphology of speci c brain regions, and a high Aβ is associated with poor cognitive function and small hippocampal volume in cognitively normal individuals [26].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on MDD using QSM reported high magnetic susceptibility in the putamen, hippocampus, and thalamus, which is not in agreement with the current results [ 28 ]. Further, prior research reported a decrease in magnetic susceptibility in the globus pallidus, left putamen, and left thalamus of first-episode schizophrenia patients [ 30 ] and observed high magnetic susceptibility bilaterally in the putamen of chronic schizophrenia patients [ 31 ]. The reason for these differences may be that previous study was not an atlas-based analysis using MNI, but a manual ROI analysis [ 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only a few studies on psychiatric disorders examine the relationship between structural subcortical volume changes and magnetic susceptibility; however, research indicates a negative correlation between volume and magnetic susceptibility in the hippocampus in schizophrenia patients [ 31 ]. Increased magnetization rates are not solely determined by iron deposition; a reduction in diamagnetic myelin also contributes to this increase.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The latter has proven valuable for presurgical mapping of deep gray nuclei targets in deep brain stimulation. 30,[35][36][37][38][39] QSM is also utilized to study imbalances in neurotransmitter levels or metabolism in psychiatric disorders such as psychosis 40,41 and depression 42,43 and to investigate neural mechanisms through which alcohol affects the brain. [44][45][46] An important feature of QSM, when compared to, for example, R 1 or R 2 relaxometry, is that its results may be less independent of field strength and scanner manufacturer when a consistent reconstruction QSM pipeline is used.…”
Section: Introductionmentioning
confidence: 99%